Diskriminasi Terhadap Etnis Tionghoa di Indonesia dalam Konten Video Investigasi Bondo Wani (MLI) pada Episode 2 Tentang Jawa vs Tionghoa di Surabaya - Reiga Pinovelius; Altobeli Lobodally (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
Discrimination against Chinese Ethnic always becomes a controversial issue for many parties and even appears to be an economic value for a number of mass communication products. This study reveals Discrimination against Chinese Ethnic in Indonesia in the Bondo Wani (MLI) investigation video content in Episode 2 about Java vs Chinese in Surabaya with signs and symbols using Roland Barthes' Semiotic analysis. Researchers use the theory of Popular Culture. Researchers analyzed the data using analysis-Semiotics Roland Barthes. Researcher outlines denotations, connotations, and myths related to discrimination in investigation video content. The results show that there is a shift and consolidation of the meaning of discrimination. In society, the myth of ethnic Chinese discrimination is class division, society borders. Discrimination in the content of Bondo wani's investigation is about cross marriage which is considered forbidden. It can be concluded that ethnic Chinese are often called "Chinese" with negative connotations, as a lowly minority, and do not have nationalism.